Academic writing in graduate studies: A students' perspective. A case study - Alfonso Vargas Franco (Universitat Politècnica de València, 2016)
Conceptions, points of view and representations on the academic writing of a Colombian graduate student are described and analyzed in this paper. The aim of this study is to show the difficulties and achievements of a student as a writer, and how her identity is built in a community of graduate academic discourse which is demanding an intense and effective command of the academic writing. The design of the study is ethnographic and the data collection instruments are semi structured interview, which was transcribed and analyzed by using the discourse analysis methods, and likewise the student's research topic stated in her thesis that was interpreted through the discourse analysis as well. The results of the study showed that there is not an explicit teaching of the academic writing in graduate level reported by the informer. Besides, the results showed that writing a thesis is, in most of the cases, an isolated activity, and an articulation between the place of writing in the previous and the current level of education was not found. Finally, it was also found that the process of the academic writing was a complex issue for the informant's identity.